Extracorporeal Shockwave Lithotripsy in the Management of a Large Proximal Ureteric Stone: A Case Report - Freeg, Mohammad A H Aly; Ranade, Anu V; Muttappallymyalil, Jayakumary; Ghaffar, Tarek F A (Nepal Journal of Epidemiology, 2011)
Urinary stone disease still persists as a major health care problem due to its high prevalence. The management of patients with ureteral stones still remains under debate in several areas. There are different therapeutic approaches for ureteral stones depending on stone size, location, anatomical variations of the urogenital tract and patient performance. Extracorporeal shockwave lithotripsy (ESWL) being the main stay of treatment of choice for the stones, the management of large stone remains a point of discussion. With the latest advance in technology coupled with knowledge, there have been recent changes in therapeutic options for ureteric stones. Therefore, the treatment approaches may be individualized in order to achieve optimum outcomes. This article reports on a case of a large proximal ureteric stone with acute flank pain and hematuria managed by ESWL. Key words: Urinary stone; Ureteric stone; ESWL. DOI: http://dx.doi.org/10.3126/nje.v1i2.5144 Nepal Journal of Epidemiology 2011;1 (2):70-73